1993
DOI: 10.1111/j.1349-7006.1993.tb00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant α1→2Fucosyltransferases Found in Human Colorectal Carcinoma Involved in the Accumulation of Leb and Y Antigens in Colorectal Tumors

Abstract: Evidence indicates that the presence of aberrant α1→2fucosylation pathways is responsible for the accumulation of large quantities of Leb and Y antigens in human colorectal carcinoma. Significantly higher activities of α1→2 as well as α1→3 and α1→4fucosyltransferases were found in most of the tissues from carcinoma than in the adjacent normal tissues and in healthy subjects. α1→2Fucosyl‐transferases associated with the synthesis of Leb (Fucal→2Galβ1→3[Fucc1→4]GlcNAcβ) and Y (Fucα1→2Ga1β→4[Fucα1→3]GlcNAcβ) stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
5
34
0
Order By: Relevance
“…Here, we show that H. pylori α1,2-FucT is functional in the synthesis of both Le b and Le Y , and the synthetic pathways (Fig. 4) are similar to those found in some human cancer cells or tissues (Blaszczyk-Thurin et al, 1988 ;Yazawa et al, 1993) (Fig. 1b, unusual pathway).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Here, we show that H. pylori α1,2-FucT is functional in the synthesis of both Le b and Le Y , and the synthetic pathways (Fig. 4) are similar to those found in some human cancer cells or tissues (Blaszczyk-Thurin et al, 1988 ;Yazawa et al, 1993) (Fig. 1b, unusual pathway).…”
supporting
confidence: 84%
“…1a) are synthesized through sequential action of the α1,2-and α1,3\4-FucTs through H determinants (Avent, 1997 ;Watkins, 1995). However, unusual α1,2-FucT activity that synthesizes Le b from Le a or Le Y from Le X has been found in some human cancer cells or tissues (Blaszczyk-Thurin et al, 1988 ;Yazawa et al, 1993), and recently such an unusual (the third type) α1,2-FucT was also found in the normal cells of rabbit (Hitoshi et al, 1996).…”
Section: Fig 1 Structural Relationship Between Lewis Antigens (A) Amentioning
confidence: 99%
“…Further studies are thus necessary to help establish the enzymes involved in Le b biosynthesis in tumor tissues from non-secretor individuals. The possibility that Le b biosynthesis in non-secretors takes place via A1,2 fucosylation of Le a has been proposed [23], and the authors suggested the existence of an, as yet unidentified, aberrant, A1,2FT in cancer cells [23]. A recent report proposed that such Le a acting activity is Fuc-TIII in COLO-205 cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes, which are virtually absent in Caucasians, are thought to be caused by weak Se-type ␣1,2-fucosyltransferase activity. The molecular basis of weak Secretor phenotypes, whether weak Se-type ␣1,2-fucosyltransferase is encoded by an altered Se gene or a gene other than H and Se, has yet to be determined.Recently, aberrant ␣1,2-fucosyltransferase activity, which synthesized Le b from Le a or Le y from the Le x determinant, or both, was found in cancer cells and tissues, suggesting the possibility of a third distinct ␣1,2-fucosyltransferase gene (13,14). In the rabbit, the possibility of a third type of ␣1,2-fucosyltransferase was suggested by immunohistochemical studies on DRG neurons.…”
mentioning
confidence: 99%
“…Recently, aberrant ␣1,2-fucosyltransferase activity, which synthesized Le b from Le a or Le y from the Le x determinant, or both, was found in cancer cells and tissues, suggesting the possibility of a third distinct ␣1,2-fucosyltransferase gene (13,14). In the rabbit, the possibility of a third type of ␣1,2-fucosyltransferase was suggested by immunohistochemical studies on DRG neurons.…”
mentioning
confidence: 99%